Effect of circuit training on the sprint-agility and anaerobic endurance - Taskin, H. (The Journal of Strength and Conditioning Research, 2009)
The purpose of this study was to determine the effect of circuit training directed toward motion and action velocity over the sprint-agility and anaerobic endurance. A total of 32 healthy male physical education students with a mean age of 23.92 ± 1.51 years were randomly allocated into a circuit training group (CTG; n = 16) and control group (CG; n = 16). A circuit training consisting of 8 stations was applied to the subjects 3 days a week for 10 weeks. Circuit training program was executed with 75% of maximal motion numbers in each station. The FIFA Medical Assessment and Research Centre (F-MARC) test battery, which was designed by FIFA, was used for measuring sprint-agility and anaerobic endurance. Pre- and posttraining testing of participants included assessments of sprint-agility and anaerobic endurance. Following training, there was a significant (p < 0.05) difference in sprint-agility between pre- and posttesting for the CTG (pretest = 14.76 ± 0.48 seconds, posttest = 14.47 ± 0.43 seconds). Also, there was a significant (p < 0.05) difference in anaerobic endurance between pre- and posttesting for the CG (pretest = 31.53 ± 0.48 seconds, posttest = 30.73 ± 0.50 seconds). In conclusion, circuit training, which is designed to be performed 3 days a week during 10 weeks of training, improves sprint-agility and anaerobic endurance.